2018
DOI: 10.1590/1678-6971/eramd180061
|View full text |Cite
|
Sign up to set email alerts
|

Between Juggling, Stunts, and Antics: The Meaning of Work for Circus Artists

Abstract: Purpose: This study aimed to investigate the meanings of the work of circus artists in three dimensions, individual, organizational, and social, following the adaptation to the model of Morin (2001) proposed by Oliveira, Piccinini, Fontoura, and Schweig (2004) and Morin, Tonelli, and Pliopas (2007). Originality/value: The article stands out because it deals with a category of artists that is losing space within society, being increasingly marginalized. Given this, it becomes relevant to understand the meaning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
1
2
0
1
Order By: Relevance
“…First of all, our finding about the role of job satisfaction confirms the effect of individual dimensions of work experience in influencing the meaning of work (Medeiros et al , 2018; Janicke-Bowles et al , 2019; Steger et al , 2019). The saliency of job satisfaction is spread across several work contexts, namely, from medical professions (Lu et al , 2019) to the banking sector (Belias and Koustelios, 2014), from police officers (Julseth et al , 2011) to volunteers (Benevene et al , 2018).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…First of all, our finding about the role of job satisfaction confirms the effect of individual dimensions of work experience in influencing the meaning of work (Medeiros et al , 2018; Janicke-Bowles et al , 2019; Steger et al , 2019). The saliency of job satisfaction is spread across several work contexts, namely, from medical professions (Lu et al , 2019) to the banking sector (Belias and Koustelios, 2014), from police officers (Julseth et al , 2011) to volunteers (Benevene et al , 2018).…”
Section: Discussionsupporting
confidence: 78%
“…Recent research suggests that studies on the overlapping between hedonic and eudaimonic variables remain valid for job well-being, for example, when considering satisfaction and professional growth as equally contributing to it (Robertson and Cooper, 2011; Ochoa and Blanch, 2019). Consistently, some studies have shown that hedonic dimensions, such as positive emotions at work and job satisfaction, predicts eudaimonic well-being at work or overlaps with it (Medeiros et al , 2018; Janicke-Bowles et al , 2019; Steger et al , 2019). At the same time, some authors showed that eudaimonic dimensions of well-being are related to one another.…”
Section: Introductionmentioning
confidence: 59%
“…De esta manera, estos estudios pueden contribuir a una gestión más efectiva y satisfactoria del personal en las organizaciones, lo que a su vez puede tener un impacto positivo en los resultados empresariales. Es importante resaltar el uso en varias publicaciones cualitativas del modelo para el sentido del trabajo desarrollado por la investigadora brasileña Morin (Gripp et al, 2022;Prado et al, 2021;Medeiros et al, 2018;Petri y Vaz, 2018). Esto es un aliciente académico que fomenta el empleo de visiones teóricas locales para el desarrollo de la investigación y la producción de conocimiento del constructo, relacionándolo con el impacto hacia la gestión del capital humano en las organizaciones y en la toma de decisiones informadas para políticas públicas relacionadas con el mundo del trabajo en la región.…”
Section: Conclusionesunclassified
“…Unfortunately, the IBs of performers in circus and stunt roles are also unstudied phenomena. The limited scholarly research on these areas focused on the nature of work (Medeiros et al, 2018) and the embodied and gendered experiences of stunt performers in television and film (Banks and Steimer, 2015;Smith, 2004). Greenblatt (2021) explored the embodied nature of circus aerial performance and its overlap with BDSM.…”
Section: Ib Of Related Performers and Artistsmentioning
confidence: 99%